Extracellular ATP and Imbalance of CD4+ T Cell Compartment in Pediatric COVID-19 - Russo, Constanza; Raiden, Silvina; Algieri, Silvia; De Carli, Norberto; Davenport, Carolina; Sarli, Mariam; Bruera, María José; Seery, Vanesa; Sananez, Inés; Simaz, Nancy; Bayle, Carola; Nivela, Valeria; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Severe COVID-19 in children is rare, but the reasons underlying are unclear. Profound alterations in T cell responses have been well characterized in the course of adult severe COVID-19, but little is known about the T cell function in children with COVID-19. Here, we made three major observations in a cohort of symptomatic children with acute COVID-19: 1) a reduced frequency of circulating FoxP3+ regulatory T cells, 2) the prevalence of a TH17 polarizing microenvironment characterized by high plasma levels of IL-6, IL-23, and IL17A, and an increased frequency of CD4+ T cells expressing ROR-γt, the master regulator of TH17 development, and 3) high plasma levels of ATP together with an increased expression of the P2X7 receptor. Moreover, that plasma levels of ATP displayed an inverse correlation with the frequency of regulatory T cells but a positive correlation with the frequency of CD4+ T cells positive for the expression of ROR-γt. Collectively, our data indicate an imbalance in CD4+ T cell profiles during pediatric COVID-19 that might favor the course of inflammatory processes. This finding also suggests a possible role for the extracellular ATP in the acquisition of an inflammatory signature by the T cell compartment offering a novel understanding of the involved mechanisms.